Mn‐Catalyzed Selective Double and Mono‐N‐Formylation and N‐Methylation of Amines by using CO2. Issue 13 (4th April 2019) - Huang, Zijun; Jiang, Xiaolin; Zhou, Shaofang; Yang, Peiju; Du, Chen‐Xia; Li, Yuehui
Abstract: Functionalization of amines by using CO2 is of fundamental importance considering the abundance of amines and CO2 . In this context, the catalytic formylation and methylation of amines represent convenient and successful protocols for selective CO2 utilization as a C1 building block. This study represents the first example of selective catalytic double N ‐formylation of aryl amines by using a dinuclear Mn complex in the presence of phenylsilane. This robust system also allows for selective formylation and methylation of amines under a range of conditions. Abstract : A formyl occasion : Selective catalytic double N ‐formylation of aryl amines is accomplished by using a dinuclear manganese complex in the presence of phenylsilane. This robust system also allows for selective formylation and methylation of amines under a range of conditions.